The IAT shows no evidence for Kandinsky's color-shape associations - Makin, Alexis; Wuerger, Sophie (Frontiers in Psychology, 2013)
In the early twentieth century, the Bauhaus revolutionized art and design by using simple colors and forms. Wassily Kandinsky was especially interested in the relationship of these two visual attributes and postulated a fundamental correspondence between color and form: yellow triangle, red square and blue circle. Subsequent empirical studies used preference judgments to test Kandinsky's original color-form combinations, usually yielding inconsistent results. We have set out to test the validity of these postulated associations by using the Implicit Association Test. Participants pressed one of two buttons on each trial. On some trials they classified shapes (e.g., circle or triangle). On interleaved trials they classified colors (e.g., blue or yellow). Response times should theoretically be faster when the button mapping follows Kandinsky's associations: For example, when the left key is used to report blue or circle and the right is used for yellow and triangle, than when the response mapping is the opposite of this (blue or triangle, yellow or circle). Our findings suggest that there is no implicit association between the original color-form combinations. Of the three combinations we tested, there was only a marginal effect in one case. It can be concluded that the IAT does not support Kandinsky's postulated color-form associations, and that these are probably not a universal property of the visual system.